A Trial Study of Static Telepathology in Iran. Issue 3 (July 2018) - Hajesmaeel Gohari, Sadrieh; Bahaadinbeigy, Kambiz; Malekpour Afshar, Reza; Asadi-Shekaari, Majid
Abstract : Static telepathology is one of the telepathology methods, in which the captured images of the slides are transmitted for consultation at a later time. This study aimed to compare the diagnostic accuracy of the conventional pathology and static telepathology systems. Eighty-two cases that had been selected randomly from 4 pathology centers in the city of Kerman were diagnosed by a pathologist, first based on light microscopy and then after 2 months based on static images (2 images per case) captured by a Nikon 50i microscopic camera. The images were sent to the pathologist via e-mail. The diagnostic accuracy of the telepathology system was calculated. The light microscopic diagnoses were concordant with the telepathologic diagnoses in 71 of 82 reviewed cases. Different diagnoses of 7 cases were due to the images captured from the inappropriate location of the slides. The diagnostic accuracy of the telepathology system was 86.5%. The results of this study showed that static telepathology is very accurate and can be widely used in Iran. However, efficient implementation and use of telepathology require paying attention to different issues such as educational, legal, ethical, financial, and security and observance of the standards related to this field.